2016
DOI: 10.7717/peerj.2612
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic postconditioning and pinacidil suppress calcium overload in anoxia-reoxygenation cardiomyocytes via down-regulation of the calcium-sensing receptor

Abstract: Ischemic postconditioning (IPC) and ATP sensitive potassium channel (KATP) agonists (e.g. pinacidil and diazoxide) postconditioning are effective methods to defeat myocardial ischemia-reperfusion (I/R) injury, but their specific mechanisms of reducing I/R injury are not fully understood. We observed an intracellular free calcium ([Ca2+]i) overload in Anoxia/reoxygenation (A/R) cardiomyocytes, which can be reversed by KATP agonists diazoxide or pinacidil. The calcium-sensing receptor (CaSR) regulates intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(57 reference statements)
0
7
0
2
Order By: Relevance
“…In 2012, in a work performed in vivo and on isolated adult rat cardiomyocytes subjected to a hypoxia post-conditioning protocol, the authors suggested that the pro-apoptotic action of CaR exerted via ER stress activation was counteracted during post-conditioning by a reduction of CaR protein expression [ 221 ]. Very recently, Zhang and colleagues confirmed that ischemic post-conditioning and KATP channel agonists diazoxide and pinacidil exert a protective effect against ischemia/reperfusion injury through a mitigation of Ca 2+ overload induced by downregulation of the CaR [ 222 ].…”
Section: The Extracellular Calcium-sensing Receptor (Car)mentioning
confidence: 99%
“…In 2012, in a work performed in vivo and on isolated adult rat cardiomyocytes subjected to a hypoxia post-conditioning protocol, the authors suggested that the pro-apoptotic action of CaR exerted via ER stress activation was counteracted during post-conditioning by a reduction of CaR protein expression [ 221 ]. Very recently, Zhang and colleagues confirmed that ischemic post-conditioning and KATP channel agonists diazoxide and pinacidil exert a protective effect against ischemia/reperfusion injury through a mitigation of Ca 2+ overload induced by downregulation of the CaR [ 222 ].…”
Section: The Extracellular Calcium-sensing Receptor (Car)mentioning
confidence: 99%
“…When the structure and function of mitochondria become abnormal, cardiomyocyte apoptosis will be induced [28]. Dysfunction of energy metabolism in myocardial cells is an important pathological basis of myocardial ischemia [27], and maintaining the functional stability of mitochondria in myocardial cells and the metabolic balance of ATP can effectively alleviate myocardial injury [29,30]. He and He [31] found that resveratrol reduced mitochondrial damage in myocardial cells, inhibited inflammatory reaction, and reduced myocardial cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, Ca 2+ enters cardiomyocytes through the L-type Ca 2+ channel (LTCC) and the β-adrenergic receptor (β-AR), causing the release of a large amount of Ca 2+ from the Sarcoplasmic Reticulum (SR) through activation of the RyR and leading to contraction. However, under some pathological conditions, such as pulmonary hypertension, myocardial ischemia, and cardiac hypertrophy, CaSR expression is upregulated, leading to [Ca 2+ ] i enhancement and thus aggravating the progression of these diseases ( Guo et al, 2012 , 2017 ; Zhang et al, 2016 ). Upon review of the previous studies, it was found that CaSR contributes to cardiac hypertrophy induced by angiotensin II, Iso, and transverse aortic constriction, and the mechanism may involve [Ca 2+ ] i , the sarcoplasmic reticulum (ER), the mitochondrial death pathway and autophagy ( Wang et al, 2008 ; Lu et al, 2013 ; Liu L. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%